Case Report and Review of the Literature: A New and a Recurrent Variant in the VARS2 Gene Are Associated With Isolated Lethal Hypertrophic Cardiomyopathy, Hyperlactatemia, and Pulmonary Hypertension in Early Infancy - Kušíková, Katarína; Feichtinger, René Günther; Csillag, Bernhard; Kalev, Ognian Kostadinov; Weis, Serge; Duba, Hans-Christoph; Mayr, Johannes Adalbert; Weis, Denisa (Frontiers in Pediatrics, 2021)
Mitochondriopathies represent a wide spectrum of miscellaneous disorders with multisystem involvement, which are caused by various genetic changes. The establishment of the diagnosis of mitochondriopathy is often challenging. Recently, several mutations of the VARS2 gene encoding the mitochondrial valyl-tRNA synthetase were associated with early onset encephalomyopathies or encephalocardiomyopathies with major clinical features such as hypotonia, developmental delay, brain MRI changes, epilepsy, hypertrophic cardiomyopathy and plasma lactate elevation. However, the correlation between genotype and phenotype still remains unclear. In this paper we present a male Caucasian patient with a recurrent c.1168G>A (p.Ala390Thr) and a new missense biallelic variant c.2758T>C (p.Tyr920His) in the VARS2 gene which were detected by whole exome sequencing (WES). VARS2 protein was reduced in the patient's muscle. A resulting defect of oxidative phosphorylation (OXPHOS) was proven by enzymatic assay, western blotting and immunohistochemistry from a homogenate of skeletal muscle tissue. Clinical signs of our patient included hyperlactatemia, hypertrophic cardiomyopathy (HCM) and pulmonary hypertension, which led to early death at the age of 47 days without any other known accompanying signs. The finding of novel variants in the VARS2 gene expands the spectrum of known mutations and phenotype presentation. Based on our findings we recommend to consider possible mitochondriopathy and to include the analysis of the VARS2 gene in the genetic diagnostic algorithm in cases with early manifesting and rapidly progressing HCM with hyperlactatemia.